PENGGUNAAN ECU STANDAR DAN REMAP PADA MOTOR HONDA BEAT PGM-FI TAHUN 2014 TORSI, TENAGA, KONSUMSI BAHAN BAKAR, DAN EMISI GAS BUANG - Remon Lapisa; Rifaldo Paslah; Andrizal Andrizal; Nuzul Hidayat (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This study intends to investigate the impact of a motorbike REMAP ECU on torque, fuel consumption, and emissions. To evaluate the impact of a particular treatment on the research object, data are directly collected using the instruments chosen for the study using the experimental technique. According to the findings of treating the study object, the REMAP ECU produced the best power value of 6.8 HP, more fuel consumption, and more exhaust emissions than the normal ECU. This issue may be solved by simply advancing the ignition timing by 1°, without increasing the percentage of fuel consumption, in order to maximise combustion and provide the most power.Keywords: ECU remap, torque and power, fuel consumption, exhaust emissions.